Division of neuromuscular compartments and localization of the center of the highest region of muscle spindles abundance in deep cervical muscles based on Sihler’s staining - Wang, Danli; Chen, Peng; Jia, Fangfang; Wang, Meng; Wu, Junxi; Yang, Shengbo (Frontiers in Neuroanatomy, 2024)
The overall distribution pattern of intramuscular nerves and the regions with the highest spindle abundance in deep cervical muscles have not been revealed. This study aimed to reveal neuromuscular compartmentalization and localize the body surface position and depth of the center of the region of highest muscle spindle abundance (CRHMSA) in the deep cervical muscles.Methods: This study included 36 adult cadavers (57.7 ± 11.5 years). The curved line joining the lowest point of the jugular notch and chin tip was designated as the longitudinal reference line (line L), and the curved line connecting the lowest point of the jugular notch and acromion was designated as the horizontal reference line (line H). Modified Sihler's staining, haematoxylin-eosin staining and computed tomography scanning were employed to determine the projection points (P) of the CRHMSAs on the anterior surfaces of the neck. The positions (PH and PL) of point P projected onto the H and L lines, and the depth of each CRHMSA, and puncture angle were determined using the Syngo system. Results: The scalenus posterior and longus capitis muscles were divided into two neuromuscular compartments, while the scalenus anterior and longus colli muscles were divided into three neuromuscular compartments. The scalenus medius muscle can be divided into five neuromuscular compartments. The PH of the CRHMSA of the scalenus muscles (anterior, medius, and posterior), and longus capitis and longus colli muscles, were located at 36.27%, 39.18%,